2019
DOI: 10.1111/mcn.12778
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the UK Baby Friendly Initiative on maternal and infant health outcomes: A mixed‐methods systematic review

Abstract: Global evidence demonstrates that adherence to the Baby Friendly Initiative (BFI) has a positive impact on multiple child health outcomes, including breastfeeding initiation and duration up to 1 year post-partum. However, it is currently unclear whether these findings extend to specific countries with resource-rich environments. This mixedmethods systematic review aims to (a) examine the impact of BFI implementation (hospital and community) on maternal and infant health outcomes in the United Kingdom (UK) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
62
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 38 publications
(76 reference statements)
3
62
1
Order By: Relevance
“…Consideration of a new mother's values and needs (micro-level) was seen as very important, aligning with recent literature suggesting culturally tailored services are significant [51]. A mixed-method analysis of five qualitative studies found that BFHI may not address women's needs and cause negative emotional experiences [49]. These negative experiences were due to poor communication and attitudes by staff which included the use of judgemental language, criticism of feeding attempts, unrealistic expectations, and using discourse which may cause feelings of guilt in breastfeeding women.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Consideration of a new mother's values and needs (micro-level) was seen as very important, aligning with recent literature suggesting culturally tailored services are significant [51]. A mixed-method analysis of five qualitative studies found that BFHI may not address women's needs and cause negative emotional experiences [49]. These negative experiences were due to poor communication and attitudes by staff which included the use of judgemental language, criticism of feeding attempts, unrealistic expectations, and using discourse which may cause feelings of guilt in breastfeeding women.…”
Section: Discussionsupporting
confidence: 52%
“…Similarly, continuity of midwifery care is known to be associated with improved maternal and neonatal outcomes [46,47] including increased breastfeeding initiation [48]. Models of midwifery care facilitating relationship building between mother and midwife as well as mother and infant [48], which are practical, consistent, and family-centred, are encouraged as such models have a positive impact on breastfeeding outcomes [49]. The importance of establishing quality communication and interaction skills and its potential impact on the dissemination of information at organisational and individual levels was also highlighted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Implementation of the BFHI has continued to have a positive effect on breastfeeding and maternity practices worldwide. 10 At our academic institution, we embarked upon our Baby-Friendly journey as a large medical center providing maternity care on two campuses in two distinct, underserved areas of the Bronx in New York City (NYC).…”
mentioning
confidence: 99%